2018
DOI: 10.5539/ass.v14n6p106
|View full text |Cite
|
Sign up to set email alerts
|

Narratives as Catalysts for Transformation and Social Action Planning within the Hong Kong Indonesian Migrant Community

Abstract: This paper discusses the use of written and oral narratives, composed as classroom assignments by adult Indonesian migrant workers, sojourning in Hong Kong. Individually written narratives embody group-common elements that can be acted upon, thus becoming catalysts for personal growth and for group social action planning. Personal growth includes refocusing personal identity away from the societally imposed and devalued ‘domestic helper’, toward identities that offer self-empowerment. Redefining personal ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Training is intended to enhance competent servitude, not to provide skills that will lead to self-confidence or assertiveness when faced with a hegemonic employer. Martyn (2018aMartyn ( , 2018b found that among Indonesian workers deployed in Hong Kong, a common complaint is that the required training programs in Indonesia focus on servitude, to the detriment of the worker's legitimate rights.…”
Section: Agents Of Subservience: Acts Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Training is intended to enhance competent servitude, not to provide skills that will lead to self-confidence or assertiveness when faced with a hegemonic employer. Martyn (2018aMartyn ( , 2018b found that among Indonesian workers deployed in Hong Kong, a common complaint is that the required training programs in Indonesia focus on servitude, to the detriment of the worker's legitimate rights.…”
Section: Agents Of Subservience: Acts Of Resistancementioning
confidence: 99%
“…The training model presented in this paper is based upon data gathered in Hong Kong and Indonesia between 2005 and 2017 (Martyn 2018a(Martyn , 2018b. Those data collections took place within the context of rapidly increasing migration from Indonesia to Hong Kong.…”
Section: Introductionmentioning
confidence: 99%